点线啮合齿轮弯曲疲劳强度优化 - 黄海; 秦英奕; 陶德馨; 龙宏欣 (Jixie chuandong)
In order to improve the efficiency of point-line meshing gear design,the multiplier method is used in point-line meshing gear optimization design.Taking the actual bending fatigue strength safety coefficient of point-line meshing gear is the largest as optimization objective,the optimization mathematical model is established.A example is used to verify the method.